Mitochondrial mass and low mitochondrial membrane potential percentage of CD8+ T cell subsets are implicated with therapeutic effect in depressive disorder - Yiran Huang; Zhenni Chen; Yang Xu; Biqiong Ren; Biqiong Ren (Frontiers in Psychiatry)
BackgroundDepression involves immune-inflammatory responses and mitochondrial dysfunction in its pathophysiology. However, the association between mitochondrial alterations in T lymphocytes and clinical treatment responses in depression remains unclear.MethodsForty hospitalized patients diagnosed with depression participated in this study, and peripheral blood samples were collected upon admission and discharge. Flow cytometry was used to monitor the frequency of T-lymphocyte subpopulations in depressed patients, mitochondrial mass (MM) and low mitochondrial membrane potential (MMPLow, %) was calculated by using the lymphocyte mitochondrial function analysis software (patented technology) in conjunction with the median fluorescence intensity of each subpopulation. Patients were further stratified into routine-term hospitalization (≤21 days) and long-term hospitalization (>21 days) groups to explore potential associations between hospitalization duration and mitochondrial changes.ResultsThe proportions of CD4+ and CD8+ T-cell subsets remained stable before and after treatment, while absolute counts of CD4+ central memory T (Tcm), CD4+ effector memory T (Tem) and CD8+ Tem significantly declined (P < 0.05). In terms of mitochondrial function, MM was significantly increased in CD4+ Tcm, CD8+ naïve T (Tn), CD8+ Tcm, CD8+ effector T (Tef), and CD8+ Tem subsets after treatment (P < 0.05), with no significant changes in CD4+ T subsets. Correspondingly, MMPLow significantly decreased in CD4+ Tn, CD8+ Tn, CD8+ Tcm, and CD8+ Tem cells (P < 0.05), suggesting improved mitochondrial polarization. Exploratory subgroup analysis based on hospitalization duration revealed that these mitochondrial improvements were predominantly observed in the routine-term hospitalization group, whereas no significant changes were detected in the long-term hospitalization group.ConclusionOur results suggest that mitochondrial alterations in CD8+ T-cell subsets may represent immunometabolic adaptations accompanying clinical improvement in depression. MM and MMPLow in CD8+ T lymphocytes may serve as preliminary biomarkers for assessing therapeutic response in depression.